Cataloging the genetic diversity of birds in Kars-Iğdır region with global comparisons - Ebeoğlu, Nadin. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2011., 2011)
Loss of biodiversity, especially genetic diversity, is among the main problems of the modern times. Birds which are found nearly all habitat types are particularly sensitive to environmental changes. Caucasus endemic bird area that is partly located in Turkey is also threatened with habitat loss. More than 75% of all bird species recorded in Turkey are believed to be found in this region. In this study, DNA barcoding technique is used for the determination of genetic diversity of bird species in the Kars-Iğdır area. Seventy three COI sequences from 33 different species and 26 different genera are newly generated for this study. 301 sequences are added from the Barcoding of Life Database. The mean intraspecific divergence for Iğdır samples was 0.62%. From 12 species, 18 new haplotypes are recorded from Iğdır samples. 26 of 33 bird species analyzed in this study had unique barcode sequences that are distinct from those found in any other species in the BOLD database. Seven species have shared or overlapping barcode sequences. Using the sequences obtained in this study, global phylogeographic comparisons are made.|Keywords: Ecological Environment, Birds, DNA barcoding, Phylogenetics.
Keywords: Birds -- Genetics -- Kars.; Birds -- Turkey -- Kars.; Birds -- Genetics -- Iğdır.; Birds -- Turkey -- Iğdır.